2022
DOI: 10.1096/fj.202101890r
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared II photobiomodulation augments nitric oxide bioavailability via phosphorylation of endothelial nitric oxide synthase

Abstract: There is solid evidence of the beneficial effect of photobiomodulation (PBM) with low-power near-infrared (NIR) light in the NIR-I window in increasing bioavailable nitric oxide (NO). However, it is not established whether this effect can be extended to NIR-II light, limiting broader applications of this therapeutic modality.Since we have demonstrated PBM with NIR laser in the NIR-II window, we determined the causal relationship between NIR-II irradiation and its specific biological effects on NO bioavailabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Additionally, because mast cells, which are essential for the NIR laser adjuvant effect above 1000 nm ( 15 ), used in this study, are generally located in the subepithelial region of the connective tissue surrounding blood cells, smooth muscle, mucosa, and hair follicles rather than on the skin surface ( 33 ), the use of NIR light above 1000 nm, which can reach deeper structures, is convenient for eliciting the adjuvant effect. However, it has also been shown that irradiation of human umbilical vein endothelial cells with NIR light at 1064 and 1270 nm generates nitric oxide (NO), a kind of ROS ( 34 ). NO inhibits the transport of electrons in the electron transport chain and increases oxygen consumption by elevating mitochondrial membrane potential, and the proton gradient is thought to ultimately lead to enhanced ATP production ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, because mast cells, which are essential for the NIR laser adjuvant effect above 1000 nm ( 15 ), used in this study, are generally located in the subepithelial region of the connective tissue surrounding blood cells, smooth muscle, mucosa, and hair follicles rather than on the skin surface ( 33 ), the use of NIR light above 1000 nm, which can reach deeper structures, is convenient for eliciting the adjuvant effect. However, it has also been shown that irradiation of human umbilical vein endothelial cells with NIR light at 1064 and 1270 nm generates nitric oxide (NO), a kind of ROS ( 34 ). NO inhibits the transport of electrons in the electron transport chain and increases oxygen consumption by elevating mitochondrial membrane potential, and the proton gradient is thought to ultimately lead to enhanced ATP production ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NO also dilates lymphatic vessels ( 24 , 35 ) and may contribute to the dilation of intradermal capillary lymph vessels as seen in this study. Thus, it is inferred that 1270 nm NIR light activates multiple cells, such as mast cells, keratinocytes ( 15 ), and endothelial cells ( 34 ), which are abundant in deep skin locations, and that the vaccine adjuvant effect is elicited by the interaction of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ravera et al discovered that the impact of 1064 nm light on the extrinsic mitochondrial membrane complex II and mitochondrial matrix enzymes was negligible; however, it exhibited a significant effect on the transmembrane mitochondrial complexes I, III, IV, and V. [36] Yokomizo et al observed that low-power NIR-II of 1064 nm and 1270 nm augmented nitric oxide bioavailability in endothelial cells and promoted cell migration via mitochondrial retrograde signaling. [37] Another possible explanation is that water functions as the primary chromophore for infrared wavelengths above 900 nm within tissues and cells. Specifically, at 1070 nm, interactions between light and water at the nanoscale can result in physical alterations that impact ion channels on intracellular membranes, subsequently inducing cellular effects.…”
Section: Discussionmentioning
confidence: 99%
“…observed that low‐power NIR‐II of 1064 nm and 1270 nm augmented nitric oxide bioavailability in endothelial cells and promoted cell migration via mitochondrial retrograde signaling. [ 37 ] Another possible explanation is that water functions as the primary chromophore for infrared wavelengths above 900 nm within tissues and cells. Specifically, at 1070 nm, interactions between light and water at the nanoscale can result in physical alterations that impact ion channels on intracellular membranes, subsequently inducing cellular effects.…”
Section: Discussionmentioning
confidence: 99%
“…24 NIR-II light has lower energy than NIR-I light due to its lower frequency, but it can be delivered into the brain tissue more efficiently for therapeutic purposes because of its lower absorption by chromophores and light scattering than those of NIR-I light. 25,26 Thus, NIR-II light holds the potential to resolve these issues because it shows the largest penetration depth into tissues [25][26][27] and a higher efficacy in inducing NO generation 13 compared with NIR-I. Indeed, low-power 1064-to 1080-nm NIR-II light has been explored to improve cognitive and emotional functions, [28][29][30][31][32][33][34][35] modulate electroencephalogram rhythms 36 in humans, and improve cognitive impairment in Alzheimer disease model 37 in mice without any evidence of damage in tissues or physiological functions.…”
mentioning
confidence: 99%